(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The ancient history of India is mostly shrouded in darkness and for its reconstruction we have to face many difficulties. We cannot say that we suffer from meagerness of literature when there is a huge Sanskrit literature at our disposal, but what we do suffer from is the absence of historical literature. Ancient Indians, by nature, were abhorrent of keeping any record of their good deeds, which they considered to be self-praise.